Eudragit® EPO, modified with 4-phenylboronic acid groups, as a novel polymeric excipient with enhanced mucoadhesive properties - D. S. Gordeeva; S. F. Nasibullin; A. G. Karpov; V. V. Khutoryanskiy; R. I. Moustafine (Разработка и регистрация лекарственных средств)
Introduction. In the pharmaceutical technology field there is great interest in polymers with mucoadhesive properties, as they increase the drug retention time on the mucosal surface and increase the bioavailability of the drug. There are various mucoadhesive drug delivery systems: tablets, films, gels, suspensions of micro- and nanoparticles, etc. The ability to adhesion depends on the excipients, especially on their chemical structure. Molecular weight, surface charge, flexibility of the polymer chain and the presence of various functional groups play an important role. Polymers under the trade name Eudragit®, produced by the German concern Evonik Nutrition & Care GmbH, have been used in the pharmaceutical field for several decades to produce controlled-release oral dosage forms. Eudragit® EPO (EPO) is a ternary copolymer based on methacrylic acid derivatives and has mucoadhesive properties due to the presence of dimethylamino groups in its structure. The proposed chemical modification of Eudragit® EPO with a phenylboronic acid derivative, due to the presence of hydroxyl groups in their structure, leads to additional interaction with mucin oligosaccharides, providing enhanced mucoadhesive properties of this polymer.Aim. Synthesis and study of a chemically modified Eudragit® EPO using 4-bromophenylboronic acid in order to increase the mucoadhesive properties of the copolymer for use in transmucosal drug delivery systems.Materials and methods. The synthesis of chemically modified Eudragit® EPO (BEPO) was carried out for 24 hours at 50 °C, followed by purification by dialysis using a dialysis membrane (MMO = 12–14 kDa; Medicell International Ltd, UK) for 7 days and freeze drying at –50 °C and 0.05 mbar using Heto Power Dry LL 3000 (Thermo Electron Corporation, USA) for 5 days. Confirmation of the formation of ВЕРО was carried out by ATR-FTIR spectroscopy on a Nicolet iS5 spectrometer (Thеrmо Fisher Sciеntific, USA) and 1H-NMR spectroscopy on a DPX 400 MHz device (Bruker, Germany). Thermogravimetric analysis (TGA) and modulated differential scanning calorimetry (mDSC) were performed using Discovery TGA™ and Discovery DSC™ (TA Instruments, USA), respectively. The study of mucoadhesive properties was performed by the ability to retain the copolymer on the isolated sheep nasal mucosa at 37.0 ± 0.5 °C for 30 minutes.Results and discussion. BEPO was prepared with a substitution degree of dimethylamino groups with phenylboronic acid of 25 % (BEPO25) and 50 % (BEPO50). The yields of BEPO25 and BEPO50 were 40.70 and 30.79 %. The new characteristic band appears at 1605 cm–1 in the IR spectrum of BEPO, which indicates the attachment of phenylboronic acid to EPO. In the 1H-NMR spectrum of BEPO, the formation of additional peaks in the range of 7.8 and 7.5 ppm is observed, which are absent in the EPO spectrum, which indicates the presence of phenylboronic acid. According to TGA results the samples of boronated EPO have the thermal stability similar to the original EPO. The results of DSC analysis show that the glass transition temperature (Tg) of BEPO samples is somehow higher than the original EPO, which is probably associated with a decrease in the amount of free dimethylamino groups in the terpolymer structure. BEPO50 is retained on the surface of isolated sheep nasal mucosa for 30 minutes, while EPO is washed off with artificial nasal fluid in 5 minutes.Conclusion. The development and study of BEPO is a promising direction for further use in transmucosal drug delivery systems.